The Predestination Functions in the Structure of the Dream in Mitrush Kuteli’s Opus - Dema, Alma; Tershalla, Risvan (Journal of Education Culture and Society, 2024)
Aim. Dreams are usually understood as a mechanism to transform thoughts into images. We use the lexeme mechanism, because the way this happens is not always identifiable or decipherable, and the level of difficulty depends on the density of the symbols that need to be decoded. Dream is said to be a sequence of images, a vision or a close connection with the reality. Having in consideration these statements this paper, aims to unravel and understand the dream and function of the predestination in the long narrative “Great is the horror of Sin, Tat Tanushi of Bubëtima”, by 30’s Albanian writer Mitrush Kuteli (2011).Methods. The methods to sort out the aim are the text analysis, interpretive and comparative ones. The text analysis will involve content analysis, thematic analysis, and discourse analysis.Results. The link between life and death, as depicted through the shifts from dreams to the afterlife, offers a distinct outlook on the world. In Mitrush Kuteli’s prose, the rich transformations both mock the long-standing fear of death and invite the living to keep enjoying life’s pleasures even beyond death.Conclusions. We have made efforts to assert our thesis that in “Great is the horror of sin, Tatë Tanushi of Bubëtima” (2011) the dream has a warning function as well as a fantastic biblical one. The conclusion is both philosophical and fantastical biblical.